The Influence of Internal and External Factors on Consumer Decision-Making - Asmaul, Husna (2008)
This research examined the effect of internal and external factors on consumer decision-making. The dimension of internal factors in this research are motivation and price perception, and the dimension of external factors in this research are reference groups and family. This research had involved 273 students of Universiti Utara Malaysia in Kedah, Malaysia. Questionnaires were used as the data collection instrument. Regression analyses were performed on each research model to test the hypotheses that were formed. The results of the regression analyses generally showed that: the influence and positive relationship between internal and external factors on consumer decision-making. Also discussed the implication of study as well as several recommendations for future research.